Construction of ecological network in Suzhou based on the PLUS and MSPA models - Xu, Xinlei; Wang, Siyuan; Rong, Wenzhuo (Ecological indicators, 2023)
•Combining land use simulation model and ecological network construction methods.•Providing reference for ecological network construction in highly urbanized areas.•Building Suzhou ecological network pattern and promoting corresponding construction strategies to improve ecological quality. Building regional ecological network can alleviate the notable contradiction between land use and ecological development in the process of rapid urbanization. Suzhou is the center city of the Yangtze River Delta urban cluster and a typical water network city, but high intensity land use has fragmented its ecological space. The study firstly introduced the patch generation land use simulation (PLUS) model to simulate the land use under the ecological priority scenario in Suzhou in 2032, combining the land use data in 2002, 2012 and 2022 to provide basis for the construction of ecological network in the later stage. Secondly, the ecological sources of the four periods were identified by combining morphological spatial pattern analysis (MSPA) and landscape connectivity analysis, and the ecological corridors and nodes of each period were screened and classified by minimum cumulative resistance (MCR) model, gravity model and hydrological analysis. Then we superimposed the screened sources, corridors, and nodes to construct an ecological network pattern in Suzhou that can develop in harmony with the land use dynamics. Finally, the degree of optimization was verified by the network structural evaluation in comparison with the ecological network in 2022. The results indicate that (1) Suzhou has the largest area of water among the land use types, with good ecological substrate. Under the guidance of the ecological green development strategy, the woodland and grassland areas will slightly increase in 2032. The overall land use pattern will generally remain consistent with that in 2022, and landscape fragmentation will be mitigated. (2) A total of 23 ecological sources are identified, mainly located near Taihu Lake, Yangcheng Lake and Yangtze River. Among them, Taihu Lake is the most important ecological source. 76 ecological corridors are screened, including 31 construction corridors, 22 protected corridors and 23 potential corridors, mostly water corridors. 54 ecological nodes are selected, divided into 21 general strategic points, 12 potential strategic points, 11 restorative strategic points and 10 break points. (3) The plan forms an ecological spatial pattern of “three cores, four pieces, multiple corridors and multiple sources” and proposes corresponding refined management measures to promote sustainable development in the Yangtze River Delta region. In addition, this study aims to propose a framework for ecological network construction coupled with land use simulation, which can provide new ideas for ecological construction of similar regions affected by urbanization around the globe.